Analyzing Non-Functional Requirements (NFRs) beyond Requirements Engineering - Dongmo, Cyrille (Engineering, Technology & Applied Science Research, 2025)
The development of Non-Functional Requirements (NFRs) alongside functional ones has long been the concern of both researchers and software engineers. The main purpose is to derive means to propagate the influence of NFRs throughout the different phases of the software development process. Despite the important progress made through Goal-Oriented Requirements Engineering (GORE) techniques, in terms of requirements elicitation, analysis, and operationalization of goals specifying NFRs, the inherent non-deterministic character of NFRs makes it very hard to anticipate at the requirements phase their impact on subsequent development phases. Thus, at a given phase of development, the actions required to satisfy an NFR, known as Non-Functional actions (NF-actions), depend on various factors, including the actions performed at the previous step as well as the type and nature of the object influenced by the NFR. This study proposes the concept of Complementary Non-Functional Actions (CNF-Actions) to facilitate the analysis of NFRs throughout the Software Development Life Cycle (SDLC). The application of the concept to a theoretical case study of an electronic voting system demonstrated its ability to facilitate the analysis of NFRs while developing the functional requirements and, therefore, contributing to extending the analysis of NFRs to other software phases of the SDLC.